The Examination of the Concept of Health Literacy through Bibliometric Analysis Method - Dilek Kolca; Selahattin Caner (Journal of Education in Science, Environment and Health)
The concept of health literacy has been defined by the World Health Organization for 25 years. During this period, thousands of publications related to health literacy have been produced in the literature. The aim of this study is to examine publications from the last 10 years concerning the concept of health literacy and to identify topics associated with health literacy in these studies. This article provides a general overview of research conducted on the concept of health literacy using bibliometric methods. The Web of Science (WoS) database was utilized as the data source for gathering information. Over the last 10 years, it has been determined that there have been 17,864 studies conducted on health literacy. This study has examined the distribution of these studies by year, author names, the most frequently used 20 keywords, and the relationships between these keywords. The results of the bibliometric analysis indicate that a variety of topics related to health literacy have been explored. Among these, the most prevalent ones include mental health literacy, health improvement, and mental health. In order to comprehend the concept of health literacy, it is essential to accurately identify the associated sub-concepts. Clearly elucidating the multifaceted relationship between these identified sub-concepts and health literacy is of great importance. The presence of diverse publications in the literature related to sub-concepts associated with health literacy highlights the need to examine these publications, providing a basis for planning future studies.